Singularly perturbed problems with rapidly oscillating inhomogeneities in the case of discrete irreversibility of the limit operator - Bobodzhanov, А. A.; Kalimbetov, B.T.; Safonov, V.F.; Tuychiev, O.D. (Karagandy University of the name of academician E.A. Buketov, 2025)
We consider a linear singularly perturbed differential system, one of the points of the spectrum of the limiting operator of which goes to zero on some discrete subset of the segment of the independent variable. The problem belongs to the class of problems with unstable spectrum. Previously, S.A. Lomov’s regularization method was used to construct asymptotic solutions of a similar system. However, it was applied in the case of absence of fast oscillations. The presence of the latter does not allow us to approximate the exact solution by a degenerate one, since the limit transition in the initial system when a small parameter tends to zero in a uniform metric is impossible. Therefore, when constructing the asymptotic solution, it is necessary to take into account the effects introduced into the asymptotics by fast oscillations. In developing the corresponding algorithm, one could use the ideas of the classical Lomov regularization method, but considering that its implementation requires numerous calculations (e.g., to construct the main term of the asymptotics in the simplest case of the second-order zero eigenvalue of the limit operator one has to solve three algebraic systems of order higher than the first), the authors considered it necessary to develop a more economical algorithm based on regularization by means of normal forms.
Keywords: singularly perturbed problem; normal form; discrete irreversibility of the operator; instability of the spectrum; regularized asymptotics; asymptotic solution; solvability of iterative problems; limit transition